2010
DOI: 10.1186/1743-422x-7-181
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular characterization of genome segments 1 and 3 encoding two capsid proteins of Antheraea mylittacytoplasmic polyhedrosis virus

Abstract: BackgroundAntheraea mylitta cytoplasmic polyhedrosis virus (AmCPV), a cypovirus of Reoviridae family, infects Indian non-mulberry silkworm, Antheraea mylitta, and contains 11 segmented double stranded RNA (S1-S11) in its genome. Some of its genome segments (S2 and S6-S11) have been previously characterized but genome segments encoding viral capsid have not been characterized.ResultsIn this study genome segments 1 (S1) and 3 (S3) of AmCPV were converted to cDNA, cloned and sequenced. S1 consisted of 3852 nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Moreover, our results revealed that VP2 interacted with VP1 (Fig. S1c), which is consistent with the report that VP2 maintains the stability of the capsid shell (Chakrabarti et al , 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our results revealed that VP2 interacted with VP1 (Fig. S1c), which is consistent with the report that VP2 maintains the stability of the capsid shell (Chakrabarti et al , 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The RNA-dependent RNA polymerase (RdRp), which is a main component of transcriptase enzyme complexes, attaches to the inner surface of the capsid shell at the icosahedral fivefold vertices (Xia et al , 2003; Zhang et al , 1999). VP2 is associated with the CSPs as an inner capsid to maintain the stability of the capsid shell (Chakrabarti et al , 2010). VP4 binds to viral RNA and helps in replication and transcription through ATP binding and hydrolysis (Chavali et al , 2008), but its localization on the particle remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The deduced amino acid sequence encoded by S1 shows greatest homology to P2 of Heliothis armigera cypovirus 5 (HaCPV-5), encoded by its genomic segment 2 (GenBank accession number: YP_001883322). It is also similar (26%) to the minor capsid protein of AmCPV-4, encoded by its genomic segment 1 [19]. The minor capsid protein of AmCPV-4 associates with the major capsid protein to maintain its stability [19].…”
Section: Resultsmentioning
confidence: 96%
“…It is also similar (26%) to the minor capsid protein of AmCPV-4, encoded by its genomic segment 1 [19]. The minor capsid protein of AmCPV-4 associates with the major capsid protein to maintain its stability [19].…”
Section: Resultsmentioning
confidence: 96%
“…Abundant evidence exists that the CSP monomers of BmCPV could assemble themselves into virus-like particles (VLPs) [10]. In addition to BmCPV, many other viruses have similar abilities, such as the VP1 protein of norovirus, the VP1 and VP3 proteins of Antheraea mylitta CPV, and the VP2 and VP3 proteins of rotaviruses [11][12][13]. VLPs have received increasing interest for their biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%